1984
DOI: 10.1002/1097-0142(19840401)53:7<1555::aid-cncr2820530723>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Urinary cytology and bladder cancer. The cellular features of transitional cell neoplasms

Abstract: Urinary cytology is increasingly accepted as a diagnostic tool in the detection and follow‐up of patients with bladder cancer. Its potential value has been reduced, however, by the relative inexperience of most pathologists in the examination of urinary specimens, and by the lack of cellular criteria specifically reflecting the morphology of low‐grade papillary and flat lesions of bladder epithelium. The cytologic features of urothelial lesions, including papillary transitional cell carcinomas and flat urothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
1
6

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(88 citation statements)
references
References 16 publications
3
78
1
6
Order By: Relevance
“…12 In addition, we used bladder wash-out specimens, which have been shown to yield a higher sensitivity com- pared with voided urine specimens. 3 Compared with the high sensitivity, the specificity of cytology in our study was lower than that reported previously. 14 All 10 patients who had presumed false positive urinary cytology had a past history of bladder carcinoma.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…12 In addition, we used bladder wash-out specimens, which have been shown to yield a higher sensitivity com- pared with voided urine specimens. 3 Compared with the high sensitivity, the specificity of cytology in our study was lower than that reported previously. 14 All 10 patients who had presumed false positive urinary cytology had a past history of bladder carcinoma.…”
Section: Discussioncontrasting
confidence: 88%
“…2 Its sensitivity is about 70% but decreases to 30 -50% for low-grade tumors. 3 Recently, a variety of urinary markers purported to be more sensitive than urine cytology have been investigated. 4 A common problem of these markers is that, when they demonstrate reasonable-to-good sensitivity, their specificity remains relative low.…”
mentioning
confidence: 99%
“…Over the decades, several classification schemes for reporting urine cytology have been proposed and the nomenclature has evolved in accordance with changes in the histologic classification of the bladder cancers. [1][2][3][4][5] However, unlike cervical cytology, there has not been widespread acceptance and use of any particular reporting scheme for urine cytology studies. The Johns Hopkins Hospital Template for Reporting Urine Cytology is the foundation for the newly proposed "Paris classification for reporting urine cytology" which has proposed 7 diagnostic categories for urine cytology samples, including negative for urothelial atypia or malignancy (NUAM); atypical urothelial cells of undetermined significance (AUC-US); atypical urothelial cells, cannot exclude high-grade urothelial carcinoma (AUC-H); high-grade urothelial carcinoma (HGUC); low-grade urothelial carcinoma (LGUC); other (squamous carcinoma, adenocarcinoma, etc.…”
Section: Introductionmentioning
confidence: 99%
“…TCCs comprise more than 90% of the diagnosed bladder tumors in the Western hemisphere and are divided broadly into papillary (growing into the lumen of the bladder) and flat lesions that arise and progress through different genetic alterations (4). Bladder tumors are diagnosed routinely by cytoscopy, which give important information on multifocality, appearance, and size (5,6). Cytoscopy is essential for resection and provides valuable material for pathological observation and research purposes.…”
mentioning
confidence: 99%